Environmental, Economic and Energy (3E) Life Cycle Assessment of Thermal Insulating Rendering Mortar using cork as lightweight aggregate - Silvestre, José D. (2016)
The analysis of the 3E (environmental, economic and energy) life cycle performance of a TIRM (Thermal Insulating Rendering Mortar), using cork as lightweight aggregate, was made considering its application in the external wall of a flat of a base model building. A com- parison was made between the solution that has been energetically rehabilitated with the application of TIRM and the reference wall without any intervention. The comparison unit was one m2 of external wall for a 50 year study period, and the environmental impacts, and the energy and economic costs and savings were quantified for both alternatives. This study showed that reference walls (without TIRM) present the worse energy performance during the use stage (energy used for heating and cooling). On the other hand, the walls that had their energy performance improved (with TIRM) present a better energy perfor- mance, resulting in lower environmental and economic impacts (reductions from 1% to 28% in costs, in carbon emissions, and in non-renewable energy consumption during the use stage, depending on the thickness and position of the layers of TIRM applied). However, the improved walls present environmental and economic impacts during production, transport to site and appli- cation into the building that are not considered in the reference walls, due to the removal of the ancient coat- ing and the application of TIRM. Finally, the comparison between reference wall and the walls with TIRM showed that although renewable ma- terials are more expensive, reference wall tends to be more costly when energy requirements for heating and cooling are analysed over a 50 year period.